Paper Electrophoresis of Fibrinogen and its Products - Salafsky, B; Loomis, T. A (Thrombosis and Haemostasis, 1963)
The plasma protein, fibrinogen, has been prepared in a relatively pure form in this laboratory. Utilizing paper electrophoresis this protein has been studied. Under normal conditions fibrinogen does not show migration from the origin; however, in the presence of the non-ionic detergent, Triton X-100, migration is noted at several pH values. The clotted product, fibrin, does not demonstrate migration from the origin under any condition. Several intermediates of the clotting sequence were also studied by paper electrophoresis in the presence and absence of the detergent and urea at several pH values. The results obtained are discussed with regard to the current hypothesis of clotting, and the products present under various conditions.